Determinants of second pregnancy among pregnant women: a hospital-based cross-sectional survey in China. Issue 3 (27th March 2017) - Xu, Xianglong; Zuo, Hanxiao; Shi, Zumin; Rao, Yunshuang; Wang, LianLian; Zeng, Huan; Zhang, Lei; Sharma, Manoj; Reis, Cesar; Zhao, Yong
Abstract : Objectives: This study aimed to explore determinants of second pregnancy and underlying reasons among pregnant Chinese women. Design: The study was a population-based cross-sectional survey. Setting: 16 hospitals in 5 provinces of Mainland China were included. Participants: A total of 2345 pregnant women aged 18 years or above were surveyed face to face by investigators between June and August 2015. Main outcome measures: The pregnancy statuses (first or second pregnancy) and reasons for entering second pregnancy. Results: A total of 1755 (74.8%) and 590 (25.2%) women in their respective first and second pregnancies were enrolled in this study. The most common self-reported reasons for entering second pregnancy among participants included the benefits to the first child (26.1%), love of children (25.8%), adoption of the 2-child policy (11.5%), concerns about losing the first child (7.5%) and suggestions from parents (7.5%). Pregnant women with low (prevalence ratio (PR) 1.96; 95% CI 1.62 to 2.36) and moderate education level (PR 1.97; 95% CI 1.65 to 2.36) were more likely to have a second pregnancy than their higher educated counterparts. Income was inversely associated with second pregnancy. However, unemployed participants (PR 0.79; 95% CI 0.66 to 0.95) were less likely to enter a second pregnancy than those employed. Women with moderate education were 3 times more likely to have a second child following the '2-child policy' than the low education level subgroup. Conclusions: 1 in every 4 pregnant women is undergoing a second pregnancy. The benefits of the firstborn or the love of children were the key drivers of a second pregnancy. Low socioeconomic status was positively associated with a second pregnancy as well. The new 2-child policy will have an influence on China's demographics.